A PRAGMATICS ANALYSIS OF COMMANDS IN SURAH AN-NISA BY SAHEEH INTERNATIONAL - Siti Sulikah; Susanto; Ayu Riski Septiana (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2018)
The aims of this research are to know the types and the dominant form of command speech acts in Surah An-Nisa by Saheeh International. The researcher uses descriptive qualitative study exactly document analysis as a research design. The subject of this research is the script of Surah An-Nisa. It is used documentation in collecting the data and to make easier in gaining the data the researcher also use table analysis and formula. The result of this research showed there are one types of command speech acts in Surah An-Nisa, named direct speech acts. Meanwhile, the dominant form of command speech acts in Surah An-Nisa is imperative which gain high frequency of occurrence